Effects of Porosity and Boron Reinforcement in AISI 316L Stainless Steel for Biomedical Applications - Aksakal, Bunyamin; Aslan, Naim; Fidan, Ferzan (My University, 2024)
AISI 316L stainless steel (SS) is one of the most widely used biomaterials in the manufacture of implants and biomaterials. It has advantages over equivalent biomaterials such as low cost, good mechanical properties and biocompatibility. The pores found in porous biomaterials provide mechanical interlock, ensuring strong attachment of the implant to the tissue. In this study, 20%, 30% and 40% by volume of polyvinyl alcohol (PVA) and Boron powder were added into 316L powder to obtain porous SS implant. To investigate the effect of porosity and boron effect on the stainless-steel implant material, the samples produced in PVA and Boron added groups, were sintered at 1180 oC under an argon atmosphere. With the evaporation of PVA in the structure, porous and boron added samples were obtained in two groups. Finally, the samples were subjected to Brinell hardness and compression tests and analyzed by SEM, EDS and XRD. As a result of the hardness tests, the highest values were measured as 37.006, 31.32, 25.28 HB. 39.5, 34.5, 26.2 MPa strengths were measured for 20%, 30% and 40% porous samples respectively.
Keywords: Mechanical properties; boron; powder metallurgy; AISI 316L stainless steel; space holder